Checkpoint inhibitor-related renal vasculitis and use of rituximab. Issue 2 (22nd July 2020) - Mamlouk, Omar; Lin, Jamie S; Abdelrahim, Maen; Tchakarov, Amanda S; Glass, William F; Selamet, Umut; Buni, Maryam; Abdel-Wahab, Noha; Abudayyeh, Ala
Abstract : The percentage of patients with cancer eligible for checkpoint inhibitor (CPI) therapy has increased rapidly over the past few years and approaches 45%. As a result, more cases of CPI-related nephrotoxicity, including a rare subset with vasculitis, are being reported. To elucidate the clinical presentation of CPI-associated renal vasculitis and its possible mechanisms, treatment options and prognosis, we describe cases from a comprehensive cancer center and reviewed the literature for similar cases. We retrospectively reviewed the charts of all patients with cancer from 2014 to 2020 who were diagnosed with CPI-related nephrotoxicity and underwent a kidney biopsy. We identified five cases of renal vasculitis: three patients were diagnosed with seronegative antineutrophil cytoplasm antibody (ANCA)-associated vasculitis, one case with seropositive ANCA-associated vasculitis and one case was diagnosed with IgA vasculitis. Of these cases, four patients were receiving nivolumab, and one patient was receiving tremelimumab. All patients had microscopic hematuria, four out of five patients had negative ANCA serology, one patient had concurrent lung involvement and positive ANCA serology, and all had severe acute kidney injury with creatinine >4.50 mg/dL on diagnosis. All patients were treated by discontinuing CPI and initiating corticosteroids and rituximab. Three patients received plasmapheresis; two of these required renal replacement therapy including the patient with lung involvement. All patients after rituximab had a partial or complete renal response. Two patients died within 8 months of diagnosis due to malignancy progression. None of the patients had a relapse of vasculitis. We demonstrated that CPI can be associated with different types of renal vasculitis that are predominantly ANCA negative and manifest as severe acute kidney injury. Despite the lack of strong evidence, treatment similar to treatment of primary seropositive ANCA-associated vasculitis with corticosteroids and rituximab is well tolerated with favorable renal outcomes.